The association of clinical and structural knee osteoarthritis with physical activity in the middle-aged population: the NEO study. Issue 11 (November 2021) - Terpstra, S.E.S.; van der Velde, J.H.P.M.; de Mutsert, R.; Schiphof, D.; Reijnierse, M.; Rosendaal, F.R.; van de Stadt, L.A.; Kloppenburg, M.; Loef, M.
Summary: Objective: To investigate if knee osteoarthritis (OA) is associated with lower physical activity in the general middle-aged Dutch population, and if physical activity is associated with patient-reported outcomes in knee OA. Design: Clinical knee OA was defined in the Netherlands Epidemiology of Obesity population using the ACR criteria, and structural knee OA on MRI. We assessed knee pain and function with the Knee Injury and Osteoarthritis Score (KOOS), health-related quality of life (HRQoL) with the Short Form-36, and physical activity (in Metabolic Equivalent of Task (MET) hours) with the Short Questionnaire to Assess Health-enhancing physical activity. We analysed the associations of knee OA with physical activity, and of physical activity with knee pain, function, and HRQoL in knee OA with linear regression adjusted for potential confounders. Results: Clinical knee OA was present in 14% of 6, 212 participants, (mean age 56 years, mean BMI 27 kg/m 2, 55% women, 24% having any comorbidity) and structural knee OA in 12%. Clinical knee OA was associated with 9.60 (95% CI 3.70; 15.50) MET hours per week more physical activity, vs no clinical knee OA. Structural knee OA was associated with 3.97 (−7.82; 15.76) MET hours per week more physical activity, vs no structural knee OA. In clinical knee OA, physical activity was not associated with knee pain, function or HRQoL. Conclusions: Knee OA was not associated with lower physical activity, and in knee OA physical activity was not associated with patient-reported outcomes. Future research should indicate the optimal treatment advice regarding physical activity for individual knee OA patients.